A cheap and quick method for DNA-based sexing of birds - Quintana, Flavio Roberto (2008)
Although the collection of air-dried blood samples on filter paper has been used for field work as a routine, it has required the use of special and expensive types of paper. In the present manuscript the use of common filter paper to collect and store air-dried bird blood samples is validated for its use in DNA based sexing techniques with a very simple method avoiding DNA purification for PCR. This method not only simplifies the laboratory work but also does not add any additional cost for DNA-based sexing techniques. The method was tested and successfully employed for sex determination by molecular techniques on blood samples taken on common filter paper during different field trips from four seabird species.